The politics of fame - Burns, Eric (Rutgers University Press, 2019)
"The Politics of Fame looks back on shifting trends in the culture and shifting currents in the human psyche that have compelled so many Americans to kneel before the thrones of so many strangers in so many different ways for so many years past and so very many to come"--